Lecture by Professor Hugh Brody for the World Oral Literature Project Occasional Lecture Series - Brody, Hugh (World Oral Literature Project, 2010)
PDF poster and MPEG4 video file In 1996, a small group of Bushmen, known as the ≠Khomani San, launched a claim to South Africa's second most important National Park. This was one of the first such land claims in Africa, and led to research, negotiation and, in 1999, a settlement. A set of research projects - recording oral histories, mapping relationships to land and resources, filming with the community - put together the land claim, and then monitored its consequences. In this lecture, Hugh Brody, who co-ordinated the research projects with the ≠Khomani San from 1997-2008, will describe the process and invite discussion of how the results of such work can have maximum value, both for the people who told the stories and made the claim, and for those who wish to draw on and analyse the materials. Professor Brody is the Canada Research Chair in Aboriginal Studies at the University of the Fraser Valley and an Associate of the Scott Polar Research Institute at the University of Cambridge. He has worked with governments and indigenous communities on land claims issues in Canada and South Africa since the 1970s. He was an adviser to the Mackenzie Pipeline Inquiry, a member of the World Bank's Morse Commission and chairman of the Snake River Independent Review, all of which involved encounters between large-scale development and indigenous communities. World Oral Literature Project: an urgent global initiative to document and make accessible endangered oral literatures before they disappear without record